Wildlife Science: Linking Ecological Theory and Management Applications - Fulbright, Timothy (CRC Press, 2009)
Consciously or not, wildlife managers generally act from a theoretical basis, although they may not be fully versed in the details or ramifications of that theory. In practice, the predictions of the practitioners sometimes prove more accurate than those of the theoreticians. Practitioners and theoreticians need to work together, but this proves difficult when new management ideas and cutting-edge ecological theory are often published in separate scientific outlets with distinctly different readerships.